The Changing Phases of Power and Civil Administration in Benin Empire Before Colonialism - Victor Osaro Edo (Journal of Global Initiatives, 2010)
The paper examines the structure, nature and character of governance and civil administration in Pre-colonial Benin up to the period of its loss of independence to British colonial administration. It analyses the processes of change in Benin from the era of the Ogisos through the period of the republican administration to the establishment of monarchical system of government. Benin's history from the earliest times to the beginning of colonial rule was dynamic and witnessed monumental changes in the structure and character of the empire. The monarchy had its fair share of the turbulence, but it remained the most resilient of all traditional institutions. The monarchy provided the pivot around which the forces of change gravitated; setting the pace and dictating the direction of its dynamism.